The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1365-2141.2008.07126.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in haemoglobin E beta‐thalassaemia

Abstract: SummaryHaemoglobin E b-thalassaemia is the commonest form of severe thalassaemia in many Asian countries, but little is known about its natural history, the reasons for its clinical diversity, or its optimal management. Despite its frequency, haemoglobin E b-thalassaemia is often managed in an illdefined and haphazard way, usually by demand transfusion. We studied a cohort of Sri Lankan patients with haemoglobin E b-thalassaemia over 5 years, and identified several genetic and environmental factors possibly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 38 publications
2
85
0
1
Order By: Relevance
“…31,32 As shown in our data and previous studies, 4,22 the phenotypic heterogeneity occurs within a narrow range of hemoglobin levels, with the pretransfusion hemoglobin of the severe group being only slightly lower than the steady-state hemoglobin levels in the moderate groups. 4 For economic and related reasons, including compliance, it has not been possible to maintain the pretransfusion Hb levels above the 9 g/dL range, as is more usual practice in severe Figure 1.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…31,32 As shown in our data and previous studies, 4,22 the phenotypic heterogeneity occurs within a narrow range of hemoglobin levels, with the pretransfusion hemoglobin of the severe group being only slightly lower than the steady-state hemoglobin levels in the moderate groups. 4 For economic and related reasons, including compliance, it has not been possible to maintain the pretransfusion Hb levels above the 9 g/dL range, as is more usual practice in severe Figure 1.…”
Section: Discussionsupporting
confidence: 54%
“…Mean Hb levels in moderate patients (6.35 g/dL) did not differ significantly from the pretransfusion levels in the severe group (5.79 g/dL; P 5 .140), as observed previously. 4,22 Likewise, HbF% did not differ between the 2 groups. Compared with patients with moderate phenotypes, patients with severe phenotypes had significantly greater iron loading and higher ALT but did not show evidence of increased erythroid drive or erythropoiesis (EPO, sTfR, and GDF15).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Ineffective red cell production by the bone marrow (ineffective erythropoiesis) forces expansion of the hematopoietic tissue outside the marrow medulla and leads to hematopoietic compensatory involvement, mostly in the form of masses, of other regions in the body-the phenomenon termed extramedullary hematopoiesis [18]. Olivieri et al [19] in a review of 109 patients with Ebthalassemia, reported only one patient had a fracture occurred without significant trauma and severe facial deformity was observed in only two patients. Eleven (15.28 %) patients had developed VTE.…”
Section: Discussionmentioning
confidence: 99%
“…This probably negated the need for a routine antibacterial and anti-malarial prophylaxis. Olivieri et al [19] in a review of 109 patients with Eb-thalassemia, reported only one splenectomized patient with severe lifethreatening infections. The predisposing factors of infections in thalassemia include splenectomy, iron overload, anemia, and granulocyte dysfunctions [22].…”
Section: Discussionmentioning
confidence: 99%